(untitled) (Letters in Nonlinear Analysis and its Applications, 2024)
In this study, we aim to present Meir-Keeler contraction mapping results on b-metric spaces. We collect and combine considerable Meir-Keeler fixed point results on b-metric spaces and generalized b-metric spaces. We have also presented the fixed point studies in b-metric spaces via admissible mappings.